AN ANALYSIS OF MORAL VALUES IN IF I HAD YOUR FACE NOVEL - Vanila Munafionika; Zulfi Zumala Dwi Andriani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Novel contains the moral value of the story told by the author. Therefore, if I had your face novel tells the story of the lives of four women in Korea with different problems. There is only one research problem in this study, what kinds of moral value that appears in the novel if I had your face. The methodology of this research is the descriptive qualitative method. In this paper, the writer researched moral values in the novel if I had your face. The writer did several steps in collecting data, starting with reading the entire book carefully and repeatedly, then marking the sections that contained moral values, then grouping them according to the type of moral values. The result of this research after analyzing if I had your face novel, the writer found nine kinds of moral values such as Bravery, Humbleness, Honesty, Steadfastness, Sympathetic to Others, Thankfulness, Trustworthiness, Sincerity, and Kind-Hearted.